1982
DOI: 10.1021/bi00540a026
|View full text |Cite
|
Sign up to set email alerts
|

A carbon-13 NMR study of aortic lesions and cholesteryl ester rich lipoproteins from atherosclerotic rabbits

Abstract: When rabbits are fed a diet supplemented with cholesterol, their plasma cholesterol levels increased markedly and they developed atherosclerosis. Most of the plasma cholesterol exists as cholesteryl esters in very low density and low-density lipoproteins. Carbon-13 nuclear magnetic resonance (13C NMR) spectra (at 48 "C) of lipoproteins, and of arterial lesions from cholesterol-fed rabbits, are dominated by well-resolved cholesteryl ester resonances. An analysis of their line widths shows that the cholesteryl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…This indicates that most of the CEs in the plaques used for this study were liquid at or near body temperature. These results agree with the previous NMR studies that show rabbit aorta plaque CEs were either in a liquid phase 25 or that liquid and liquid-crystalline phases coexisted near body temperature. 29 …”
Section: Quantification Of Ces In Rabbit and Human Atherosclerotic Lesupporting
confidence: 93%
See 2 more Smart Citations
“…This indicates that most of the CEs in the plaques used for this study were liquid at or near body temperature. These results agree with the previous NMR studies that show rabbit aorta plaque CEs were either in a liquid phase 25 or that liquid and liquid-crystalline phases coexisted near body temperature. 29 …”
Section: Quantification Of Ces In Rabbit and Human Atherosclerotic Lesupporting
confidence: 93%
“…Peak assignments were based on previous studies. 19,25,26 Because the T 1 values for C5 and C6 carbons in noncrystalline CEs are Ͻ1 second, 25 a 5-second pulse interval time was used to allow full magnetization relaxation, which is important for quantification studies at NMR intensity. The sample temperature was controlled within 1°C by the Bruker B-VT-1000 variable temperature unit.…”
Section: Nmr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The rupture of atheromatous plaques is a major contributor to the development of myocardial infarction, and it has been demonstrated that plaque vulnerability is dependent on the biochemical characteristics of the lipid pool. 47 Natural-abundance u C-nuclear magnetic resonance (NMR) spectroscopy allows the nondestructive characterization of lipid chemical composition.…”
mentioning
confidence: 99%
“…47 Natural-abundance u C-nuclear magnetic resonance (NMR) spectroscopy allows the nondestructive characterization of lipid chemical composition. Because of its broad chemical shift bandwidth, 13 C-NMR provides more information regarding chemical constituents than 'H-NMR 810 and has been used for structural and dynamic studies of cholesteryl esters (CE), triglycerides (TG), and phospholipids (PL). "- 14 Hamilton and Cordes 15 examined plasma lipoproteins and intact ath-erosclerotic plaques in humans, demonstrating that atheroma had spectral characteristics very similar to those of thermally denatured LDLs, suggesting a comparable chemical composition.…”
mentioning
confidence: 99%